Chronická apendicitis--mizející ci bezná diagnóza? - Krska, Z; Sváb, J (Casopis lekaru ceskych, 2007)
BACKGROUND: Analysis of the literary findings and the clinical experiences of chronic appendicitis (CA) is presented. METHOD AND RESULTS: Analysis of the literary findings and study of our group of patients who were operated between years 2002 and 2004 is presented. The cohort includes 146 patients; 81% women, 19% men, aged between 14 to 72 years, average age 34 years, average age of men 46 years, women 29 years. The trend in the number of surgeries is decreasing in about 10% per year. Surgery findings: men--90% adhesions, atypical positions, findings of coprolites. Women--only 40% had macroscopical "findings". Medical history in the obscure cases (evaluable only in 50%), long-term hormonal contraception in 20%, 1-2 months after setting of hormonal contraception in 30%, intrauterine corpuscle in 10%, total negative in 40%. Effects of surgery in the group obscure surgery findings were practically always incomplete. Basic controversy in the diagnostic, in the range and in the appropriate time of surgical intervention is discussed. Surgeon also participates in the diagnostics, because the diagnosis of chronic appendicitis can come from some other medical specialists and the accuracy of indications can vary. Another aspect of the role of surgeon is the high evidence of laparoscopic methods for the diagnosis. Our results correspond with the literary sources. CONCLUSIONS: Chronic inflammation changes in the wall of the appendix bring about structural changes in the abdominal cavity. Clinical correlate exists only in the relation to the serious changes resulting from the inflammation of appendix for example: fixations, adhesions. That is why the chronic appendicitis as a clinical entity markedly receded. Problem is the restricted possibility, the range and level of investigation of right iliac region. From this point of view the rationality and professional opinion are essential in the indication to surgery.
Keywords: Male; Aged; Female; Appendicitis; Chronic Disease; Humans; chronická nemoc; lidé středního věku; Adolescent; ženské pohlaví; Middle Aged; senioři; dospělí; lidé; apendicitida; mužské pohlaví; Adult; mladiství